Advanced solutions with hot‐rolled sections for economical and durable bridges. Issue 3 (14th August 2018) - Rademacher, Dennis; Ochojski, Wojciech; Lorenc, Wojciech; Kożuch, Maciej
Abstract: Growing problems in terms of damage to bridges correlated with – in some cases huge – long‐term impacts on road traffic have shown how essential it is to ensure the durability of the infrastructure and thus the mobility of people as well as the exchange of goods. Corrosion damage can be sustainably avoided in future by employing alternative protection systems for steel and composite bridges. Both hot‐dip galvanizing with a coating thickness of at least 200 µm and weathering steel offer crucial advantages over traditional coating systems when considering the whole life cycle of a bridge: They require no maintenance, and so traffic disruption can be avoided. When using these systems in combination with hot‐rolled sections, there are further significant advantages as they render composite bridges more economical and durable, particularly when it comes to short and medium spans. Standard higher strengths with steel grade S460 allow for more economical cross‐sections, with weight‐ and cost‐savings of often 20–30 % compared with welded built‐up sections in grade S355. Sophisticated designs employing rolled sections can achieve not only small and medium spans, but also longer ones, e.g. arch bridges with spans > 100 m. This article describes new trends in Europe using hot‐rolled sections in steel and composite bridges.